HIV counselling and testing in rural Uganda: communities’ attitudes and perceptions towards an HIV counselling and testing programme - Kipp, W.; Kabagambe, G.; Konde-Lule, J. (AIDS care, 2002)
Study results on the assessment of a community-wide HIV counselling and testing programme are presented. The aim of this qualitative study was to elucidate whether HIV counselling and testing (HIV CT) was acceptable to a rural community and whether they expressed a need for it. From a total of 2,267 persons of Kigoyera Parish, western Uganda, who were HIV tested and counselled, 171 persons participated in 17 focus group discussions. Most participants expressed a strong need for HIV counselling and testing services. The counsellors were seen as competent and confidential. Community health workers were favoured as the preferred provider of HIV CT services. However, participants stressed that they should not come from the same community. Most participants felt that a HIV CT programme available only once is not enough and did not induce a change in sexual behaviour, e.g. increased condom use. They requested counselling services that are continuously offered. The study results also showed that there is a demand for HIV counselling services without being HIV tested.
Keywords: HIV counselling and testing programme; Communities’ attitudes